Effect of Time and Severity of Pruning on Growth, Flowering and Fruiting in Her (Ziziphus mauritiana Lamk.) cv. Umran - Kundu, S S; Pareek, O P; Gupta, A K (Annals of Arid Zone, 2016)
The study was conducted to know the effect of time and severity of pruning on growth, flowering. fruit setting and fruit retention on ber cv.Umran. The plants were pruned on three dates at the interval of 15 days. i.e. from 15th May to 15th June with five levels of pruning intensities. The shoot length, leaf area, per cent bud sprouting, per cent fruit set and per cent fruit retention differed significantly with various pruning treatments. From the present investigation, it was found that the plant pruned on 30 May at 15 buds, recorded maximun fruit retention per tree.